Streamlining Arabic Grammar to Facilitate Mastery of Qirâ’at al-Kutub for University Students - Ardiansyah, Ade Arip; Musthafa, Izzuddin; Syafei, Isop; Sanah, Siti (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study evaluates a streamlined approach to Arabic grammar instruction designed to help university students master Qirâ’at al-Kutub. This study uses a qualitative approach with a case study design to explore the effectiveness of a simplified Arabic grammar teaching method in facilitating mastery of Qirâ’at al-Kutub. The simplified method addresses challenges in traditional teaching, improving comprehension and application of grammar in classical texts. Using pre-test and post-test analysis, the study recorded a 20% increase in average scores (65% to 85%) and significant reductions in fi'il mudhâri' errors (40% to 10%) and i’râb errors (50% to 15%). The method proved particularly effective for students struggling with conventional approaches, with 86% reporting improved confidence and comprehension. However, participants also highlighted the need for additional resources (82%) and support for complex texts (68%). This research offers a practical, inclusive solution to Arabic grammar instruction, fostering critical reading skills and deeper engagement with linguistic heritage. Future studies should explore digital tools, interactive platforms, and longitudinal impacts to refine and expand this approach in diverse educational contexts.